The new "Hesitation Blues": initiating Mycobacterium avium complex lung disease therapy. Issue 3 (9th March 2017) - Griffith, David E.; Philley, Julie V.
The "Hesitation Blues" is a traditional blues/folk tune that was first recorded a century ago. Since that time, more than 40 artists with diverse musical pedigrees have recorded the song, ranging from Lead Belly to Doc and Merle Watson to Hot Tuna. An interesting aspect of the various recordings is that while the narrative of the song consistently expresses carnal frustration, the actual lyrics just as consistently vary from one version to the next. It is, therefore, a fitting and appropriate platform to propose further lyric modification that shifts the emphasis to the frustrating hesitation experienced by physicians who must decide about the initiation of Mycobacterium avium complex (MAC) lung disease therapy. Clinical assessment is the key element for deciding which patient with Mycobacterium avium complex needs therapy http://ow.ly/90mo3091Bkh